The Impact of Local Wisdom-Based Character Education on Student Behavior in SD Pusaka Deliserdang - Toni Ardi Rafsanjani (JELIM : Journal of Education, Language, Social and Management, 2025)
This study investigates the impact of local wisdom-based character education on student behavior at SD Pusaka Deliserdang. The research was conducted to address the growing need for culturally relevant approaches in moral education, especially in elementary school settings. Utilizing a mixed-method design, the study combined quantitative analysis of pre-test and post-test behavior scores with qualitative data from interviews, observations, and documentation. The findings reveal that the integration of local wisdom—such as traditional stories, sayings, and communal values—into character education significantly improved students’ behavior in key areas including responsibility, cooperation, discipline, respect, and honesty. Quantitative results showed a marked increase in behavior scores after a 12-week intervention, with statistically significant gains across all measured indicators. Qualitative data further supported these findings, highlighting how students internalized moral values more effectively when presented through culturally familiar narratives and examples. The study also found that teacher creativity, community involvement, and student engagement played crucial roles in the success of the program. Despite challenges in sourcing appropriate cultural materials and ensuring inclusivity, the overall impact was positive and transformative. This research underscores the importance of contextualizing moral education within students’ cultural environments and provides a model for other schools seeking to implement similar initiatives.